Error recovery training literature review: Implications for emergency field medicine. (September 2021) - Militello, Laura G.; Wagner, Eli; Winner, Jennifer; Sushereba, Christen; McCool, Jessica
Training focused on recognizing when a medical procedure has not been implemented effectively may reduce preventable battlefield deaths. Although important research has been conducted about a range of error recovery training strategies, few studies have been conducted in the context of training for high stakes, dynamic domains such as combat medic training. We conducted a literature review to examine how error recovery training has been designed in other contexts, with the intent of abstracting recommendations for designing error recovery training to support military personnel providing emergency field medicine. Implications for combat medic training include: 1) a focus on error management rather than error avoidance, 2) a didactic training component may support training engagement and mental model development, 3) an experiential component may be designed to support perceptual skill development and anomaly detection, and 4) feedback should focus on allowing learners to make errors and encouraging them to learn from errors.